Postcolonial Analysis of Cultural Identity in Selasi’s Afropolitan novel Ghana Must Go (2013) - NAOUI ,Khedidja; AOUED, Siham; SELT, Djihad Afaf (Faculty of Letters and Foreign Languages Department of English, 2019)
There are a lot of problems that mankind suffer from but the problem of cultural identity is one of the controversial issues that occupy the biggest part in postcolonial studies .especially Africans who have suffered to relocate and identify themselves in the white society .This dissertation is concerned with the issue of African cultural identity in Taiye Selasi's Ghana Must Go (2013). It attempts to investigate not only the difficulties of black people as diasporic immigrants, but also to examine their abilities to reformulate their lost identities. This study is carried through the analysis of the characters and the themes expressed in the novel relying on Postcolonial theory and the notion of Afropolitanism .In two chapters, this study will provide a theoretical frame work about post colonial theory in Africa followed by an analytical one.